China’s product-level CO2 emissions dataset aligned with national input-output tables from 1997 to 2020 - Xinbei Li; Yu Liu; Jing Zhang; Meifang Zhou; Bo Meng (Scientific Data)
Abstract Carbon emission research based on input-output tables (IOTs) has received attention, but data quality issues persist due to inconsistencies between the sectoral scopes of energy statistics and IOTs. Specifically, China’s official energy data are reported at the industry level, whereas IOTs are organized by product sectors. Valid IOT-based environmental models require consistent transformation from industry-level to product-level emissions. However, most existing studies overlook this necessary transformation, leading to substantial estimation errors. This study addresses this issue by developing a high-quality, product-level emissions dataset for China, grounded in robust product technology identification derived from IOTs. Our new emissions dataset, aligned with Chinese national IOTs, covers 29 to 34 product sectors across 7 benchmark years from 1997 to 2020. It includes data from 4 to 5 energy sectors and detailed emissions for 18 types of fossil fuels, using both IPCC-default and two China-specific emission factors. This inventory improves product-sector emission accounting and can be integrated into IOT-based climate and energy models, serving as a fundamental database for energy and emission analysis.